A strategic planning approach defining alternative counterterrorism strategies as an illustration - Davis, Lynn E. 1943-; Sisson, Melanie (RAND, 2009)
While the United States government has historically undertaken strategic reviews and produced numerous strategy documents, these have provided only very general directions for U.S. policymakers. This paper defines an approach to strategic planning and illustrates its application using the example of the critical national security topic of counterterrorism.
Includes bibliographical references
Keywords: POLITICAL SCIENCE / Political Freedom & Security / Terrorism; Politik; Terrorismus; Terrorism -- Prevention -- Government policy -- United States; Strategic planning -- United States; Bekämpfung; Strategische Planung; USA